Augmented Reality as a Pedagogical Tool in Cultural Education: A Case Study on Srimulat-Based Cultural Learning Among University Students - Wardaya, Marina; Limantara, Quina Reivaldi; Utomo, Pandu Rukmi (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study explores the potential of Augmented Reality (AR) can be used as a learning tool to help college students learn more about Srimulat, a traditional Indonesian comedy troupe that younger generations are losing interest in. As students who grew up with digital media become less interested in local performing arts, it becomes more important to include heritage content in interactive media. To fix this, an AR app was made using user-centered design principles, which focus on the needs and habits of students, and multimedia learning theory, which says that using pictures and narration together can help people understand better. The app used 3D models, voice narration, and interactive posters to show Srimulat characters. The program was used in a university exhibition and involved 68 students who took pre-test and post-test to see how much they had learned. The results showed a big increase in knowledge, with post-test scores going up by an average of 24.1 points. Additionally, 94% of participants reported enjoyment, while 91% claimed to have a better understanding of the cultural aspect. Although these statistics are positive, the study took place at a single school, and it only examined short term learning effects. Future research, in order to further support of its role in cultural education, should examine long-term learning effects, cross-cultural comparisons, and methods for integrating AR, in formal educational contexts.